Implementation of a training course increased the diagnosis of histoplasmosis in Colombia (2015)
Histoplasmosis causes a significant mortality, especially persons living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) from developing countries where access to both appropriate diagnostic methods and antiretroviral therapy are limited. A total of 81 physicians assigned to 17 Colombian departments (states) received training in the clinical, epidemiological, and diagnostic aspects of histoplasmosis. Once this training was received and during the period of October 2009-November 2012, these physicians sent biological samples for immunodiagnostic, mycological, and molecular tests from their patients with suspicion of histoplasmosis. A total of 1,536 samples from 768 patients were evaluated. Of the 768 patients studied, 463 (60%) were HIV positive, 214 (28%) HIV negative, and in 91 (12%) this diagnosis was unknown, and 538 (70%) were males. The 1,536 specimens studied comprised 722 sera, 439 blood samples, and 241 urines, which were tested by immunodiffusion (ID), culture, and antigenuria, respectively; in addition, 134 specimens were tested by performing a molecular assay. Histoplasmosis was diagnosed in 133 patients (17%). After the training, we observed more diagnoses from 27 to 44 cases per year. In this study, a significantly increased number of histoplasmosis cases reported by year were observed after implementing an educational training program. Copyright © 2015 by The American Society of Tropical Medicine and Hygiene.